2019
DOI: 10.1210/en.2019-00300
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Suppression of Milk Protein Is Involved in a Noradrenergic Mechanism in the Mammary Gland

Abstract: Stress decreases milk components such as milk protein and milk yield. The objective of this study was to investigate whether noradrenaline (NA) in milk constituted a factor associated with stress-induced changes in milk proteins such as β-casein. Breast milk obtained from eight healthy, nursing women contained NA at concentrations ranging from 12.7 to 115.5 nM. The expression of tyrosine hydroxylase (TH), a rate-limiting enzyme of NA synthesis, was observed in primary normal human mammary epithelial cells (HME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Therefore, responses mediated by these catecholamines (including in tumorigenesis [32,33,38] have been solely associated with the activation of the SNS. The present study shows that breast cells can also synthesize catecholamines, confirming previous observations in normal human mammary epithelial cells [35], and in non-tumorigenic and tumorigenic breast cell lines [35,36].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, responses mediated by these catecholamines (including in tumorigenesis [32,33,38] have been solely associated with the activation of the SNS. The present study shows that breast cells can also synthesize catecholamines, confirming previous observations in normal human mammary epithelial cells [35], and in non-tumorigenic and tumorigenic breast cell lines [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…In non-tumorigenic human breast cells, the main catecholamine produced was reported to be noradrenaline [35]. In the present study, in the tumorigenic MCF-7 cells, adrenaline was the main catecholamine detected in the conditioned medium, suggesting that the adrenaline/noradrenaline ratio may be seen as an index of tumorigenicity.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…For example, nursing mice fed a high-fat diet demonstrated an increase in milk lactose and fat content as well as differently expressed mRNAs related to central nervous system development (Chen et al, 2017). Restraint stress has been shown to reduce milk protein in lactating mice (Chiba et al, 2019) and other stressors such as social and heat stress have been shown to negatively affect lactation (Murgatroyd et al, 2015) and milk yield (Haldar & Bade, 1981) respectively. Such evidence underscores how the maternal environment may contribute to alterations in the nutritional profile of milk which may have subsequent consequences on progeny development, although effects on offspring remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%